Functional analysis reveals differential effects of glutamate and MCH neuropeptide in MCH neurons - Marc Schneeberger; Keith Tan; Alexander R. Nectow; Luca Parolari; Caner Caglar; Estefania Azevedo; Zhiying Li; Ana Domingos; Jeffrey M. Friedman (Elsevier, 2018)
Objectives: Melanin-concentrating hormone (MCH) neurons in the lateral hypothalamus (LH) regulate food intake and body weight, glucose metabolism and convey the reward value of sucrose. In this report, we set out to establish the respective roles of MCH and conventional neurotransmitters in these neurons. Methods: MCH neurons were profiled using Cre-dependent molecular profiling technologies (vTRAP). MCHCre mice crossed to Vglut2fl/flmice or to DTRfl/flwere used to identify the role of glutamate in MCH neurons. We assessed metabolic parameters such as body composition, glucose tolerance, or sucrose preference. Results: We found that nearly all MCH neurons in the LH are glutamatergic and that a loss of glutamatergic signaling from MCH neurons from a glutamate transporter (VGlut2) knockout leads to a reduced weight, hypophagia and hyperkinetic behavior with improved glucose tolerance and a loss of sucrose preference. These effects are indistinguishable from those seen after ablation of MCH neurons. These findings are in contrast to those seen in mice with a knockout of the MCH neuropeptide, which show normal glucose preference and do not have improved glucose tolerance. Conclusions: Overall, these data show that the vast majority of MCH neurons are glutamatergic, and that glutamate and MCH signaling mediate partially overlapping functions by these neurons, presumably by activating partially overlapping postsynaptic populations. The diverse functional effects of MCH neurons are thus mediated by a composite of glutamate and MCH signaling. Keywords: MCH, Sucrose preference, Body weight, Glucose metabolism, Neuropeptide, Glutamate